2008
DOI: 10.2460/javma.233.7.1105
|View full text |Cite
|
Sign up to set email alerts
|

Association of pruritus with anxiety or aggression in dogs

Abstract: An association was not detected between pruritus and aggressive, anxious, or fearful behavior in dogs. There was greater reactivity to thunderstorms or noises in glucocorticoid-treated dogs. These findings do not preclude the possibility of a relationship between certain dermatoses or pruritic conditions and behavior. However, a concurrent behavioral abnormality cannot be assumed to result from a dermatosis and be expected to resolve with treatment of only the skin disease. Dogs with behavioral disorders and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…The results of this study support acceptance of Hypothesis 2, that predicted dogs with skin allergies would exhibit more problem behaviours, lower scores for trainability and no differences for generic fearful or environmentally anxious behaviour. The lack of evidence for Hypothesis 1 supports previous findings from Klink and colleagues [36] who found no association between pruritus and generally anxious/fearful behaviour or aggression in pruritic dogs. Here, atopic dogs scored higher than controls for a number of everyday problem behaviours (mounting, coprophagia, hyperactive/restlessness, pulling excessively on the lead), comfort-seeking behaviour (attachment/attention-seeking, begging for food), behaviour likely to be directly related to pruritus (self-grooming, allo-grooming, touch sensitivity), and other repetitive behaviour.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this study support acceptance of Hypothesis 2, that predicted dogs with skin allergies would exhibit more problem behaviours, lower scores for trainability and no differences for generic fearful or environmentally anxious behaviour. The lack of evidence for Hypothesis 1 supports previous findings from Klink and colleagues [36] who found no association between pruritus and generally anxious/fearful behaviour or aggression in pruritic dogs. Here, atopic dogs scored higher than controls for a number of everyday problem behaviours (mounting, coprophagia, hyperactive/restlessness, pulling excessively on the lead), comfort-seeking behaviour (attachment/attention-seeking, begging for food), behaviour likely to be directly related to pruritus (self-grooming, allo-grooming, touch sensitivity), and other repetitive behaviour.…”
Section: Discussionsupporting
confidence: 87%
“…Antihistamines, for example, have a sedative effect and have been shown to induce cognitive impairments in learning and decision-making in humans [49]. Klinck and colleagues found that dogs treated with glucocorticoids were more likely to be reactive to loud noises and thunderstorms [36]; however, we found no difference here between cases and controls or pruritus severity for the C-BARQ scale ‘non-social fear’, which includes noise sensitivity. Dogs with epilepsy have also been shown to score lower than healthy controls for trainability and higher for excitability (also measured by the C-BARQ) [41,50], as was found here with the dogs with cAD, although no differences in the other behavioural factors found here were reported for epileptic dogs.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It has been shown that pruritus might be exacerbated by psychological disorders in humans but also that pruritus can worsen behaviour (Shaw and others 2007). The issue of the influence of pruritus as a main sign of dermatological conditions was investigated in dogs by Klinck and others (2008). They found no relationship between pruritus and aggression or anxiety, but they did find a significant increase in reactivity to potentially fearful stimuli in dogs treated with corticosteroid drugs.…”
Section: Discussionmentioning
confidence: 99%
“…41 An increased severity and frequency of dermatologic conditions has been reported among dogs with fears and anxieties, 10 and the importance of multimodal treatment addressing concurrent psychological conditions in dogs with pruritus, such as anxiety, fearfulness, or aggressive behavior, is increasingly being recognized. 42 Indeed it has been suggested that behavioral therapy in combination with psychopharmacology can be important in achieving an improvement of 50% or more in dermatologic expressions of repetitive behaviors in cats and dogs. 43 In cats, self-grooming and scratching are often immediate responses to conflict without any pathologic impact.…”
Section: Reproductive Systemmentioning
confidence: 99%